2022
DOI: 10.5530/ijpi.2022.2.35
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach of Leflunomide Nanoemulgel for Topical Drug Delivery System

Abstract: Objectives: This research's primary goals are Leflunomide (LFD) nanoemulgel formulation and characterization for topical administration. Materials and Methods: A pseudo ternary phase diagram was created utilizing castor oil, Tween 20 as the surfactant, PEG 300 as a co-surfactant, and ethanol as the cosolvent. Spontaneous emulsification was used to create LFD-nanoemulgel, which is now commercially available. Gel matrix Carbopol 934 was employed to generate nanoemulgel in the prepared nanoemulsion. Studies on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Particle size testing is carried out to determine the size of the globules formed in nanoemulgel and elmulgel. 16…”
Section: Particle Size Measurementmentioning
confidence: 99%
“…Particle size testing is carried out to determine the size of the globules formed in nanoemulgel and elmulgel. 16…”
Section: Particle Size Measurementmentioning
confidence: 99%
“…Verma and Easwari reported that 1% Carbopol hydrogel interconnected pores with different sizes that can be quite helpful in drug loading and faster drug release. 38 Thus the gel part of formulation was made using the left-out water (22%) with 1% w/v of Carbopol 934 as the gelling agent. TNL was integrated with the gel base by 10 min mixing.…”
Section: Tetrahydro Curcumin Nanoemulgel (Tnlcg) Formulationmentioning
confidence: 99%
“…The treatment was repeated for 6 cycles and the phase separation was observed. Physical conditions after the experiment were compared with before the experiment [21].…”
Section: Physical Stability Study Of Nanoemulgel and Emulgelmentioning
confidence: 99%